Aboriginal Assimilation and Nyungar Health 1948-72 - Haebich, Anna (Australian and New Zealand Society of the History of Medicine, 2012)
The policy of assimilation in mid-twentieth-century Australia holds a major place in the history of Aboriginal health. For the first time Australian governments endorsed equal citizenship for Aboriginal people with full access to mainstream medical and hospital services previously denied to them. After decades of neglect Aboriginal families could look forward to better health. Politicians were convinced that disparities in Aboriginal health would be readily assimilated into the profile of the general population. However, this case study of assimilation’s mainstreaming of health services for Nyungar people in Western Australia demonstrates that the outcome was a mix of significant advances and enduring legacies of discrimination. Improvements were frustrated by endemic racism, contested understandings of assimilation, and the government’s failure to meet its promises. A consequence was a legacy of suspicion and anxiety that continues to impact adversely on Nyungar health today.